Predictive Factors for Clinical Outcome After Direct Mechanical Thrombectomy for Anterior Circulation Large Vessel Occlusion Within 4.5 h - Nguyen, Huu An; Vu, Dang Luu; Nguyen, Quang Anh; Mai, Duy Ton; Tran, Anh Tuan; Le, Hoang Kien; Nguyen, Tat Thien; Nguyen, Thu Trang; Tran, Cuong; Dao, Viet Phuong; Pierot, Laurent (Frontiers in Neurology, 2022)
Background: Recent trials including DIRECT-MT, DEVT, and SKIP have found that direct mechanical thrombectomy (MT) is equally effective as the combination of MT and intravenous thrombolysis. However, results of the other trials, namely MR-CLEAN NO-IV and the SWIFT-DIRECT trial have failed to confirm noninferiority of direct MT versus the combination therapy. Aim: We aimed to identify prognostic factors of direct MT for anterior circulation large vessel occlusion within 4.5 hours. Materials and Methods: Data from January 2018 to January 2022 were retrospectively collected and analyzed. Adult patients with confirmed anterior circulation large vessel occlusion within 4.5 hours of onset with baseline NIHSS of ≥ 6 and baseline ASPECTS of ≥ 6 treated using direct MT within 6 hours were recruited. Results: A total of 140 patients were enrolled in the study with median age of 65.5 years (interquartile range [IQR], 59-76.5), median baseline NIHSS of 13.5 (IQR, 11-16), and median baseline ASPECTS of 8 (IQR, 7-8). Direct MT was feasible in all patients (100%). Successful reperfusion (mTICI 2b-3) was achieved in 124/140 patients (88.6%) with a low rate of complications (8/140, 5.7%). Intracranial hemorrhage (ICH) and symptomatic ICH occurred in 44/140 (31.4%) and 5/140 (3.6%), respectively. Overall, a good outcome (mRS 0-2) was achieved in 93/140 (66.4%), and mortality rate was 9.3% (13/140 patients). Using multivariate analysis, lower age (odds ratio [OR], 0.96; 95% CI, 0.92-1.00; P=0.05), low baseline NIHSS (OR, 0.82; 95% CI, 0.74-0.92; P=0.00), and absence of ICH (OR, 0.29; 95% CI, 0.10-0.81; P=0.02) were independently associated with favorable outcome. Independent predictors of mortality were baseline NIHSS (OR, 1.21; 95% CI, 1.01-1.46; P=0.04), successful reperfusion (OR, 0.02; 95% CI, 0.00-0.58; P=0.02), and ICH (OR, 0.12; 95% CI, 0.02-0.75; P=0.02). Further analysis showed that the median mRS at 90 days was significantly better in the MCA occlusion group compared to the ICA plus M1 occlusion group (1 [IQR 0-3] versus 2 [IQR 1-4]; P=0.05). Conclusions: Our findings suggest that direct thrombectomy may be an adequate clinical option for younger patients (≤ 70) experiencing proximal middle artery occlusion within 4.5 hours and who have low baseline NIHSS (≤ 14).